Um estudo experimental sobre o estilo de fala em dublagem - Brisola, Everton (2024)
Dubbing films involves replacing lines previously recorded in one language with lines in another language, based on the visual material of the scenes being filmed. It constitutes a fertile field of work, unexplored in terms of research. Given this context, the main objectives of this research are: i) to analyze the dubbing of a character by a star talent in the animated film "Tangled"; ii) to carry out a perception test to ascertain the impression made on listeners by the interpretation performed by the star talent. The secondary objectives are: i) to characterize the work of dubbing; ii) to present an overview of the dubbing activity in Brazil; iii) to survey the parameters used by Brazilian oral recording studios to select dubbing artists. The motivation for choosing the film is the fact that it has provoked several questions regarding both oral interpretation and labor issues. The research questions are: I) What can be deduced from a perceptual evaluation using semantic descriptors of the speaking style used in the dubbing of the male protagonist in the movie Tangled? II) What characteristics of professional voice use does the voice-over style demand? III) Can the characterization of the voice-over style have an impact on labor issues? As research hypotheses we postulate: I) dubbing constitutes a differentiated speech style in prosodic terms; II) the characterization of the dubbing speech style can provide subsidies for rethinking labor issues regarding the profile of professionals suitable for the profession. The analysis conducted in this work has a theoretical basis in phonetic research on speech expressiveness and speech stylistics, which allows the main prosodic characteristics of the oral interpretations in focus to be analyzed. The methodology used is experimental in nature, using perceptual analysis procedures of vocal dynamics through the application of a semantic differential test, which makes it possible to evaluate the positive or negative valence of locutions using semantic descriptors. Interviews were also conducted with dubbing professionals. As a result, we highlight the characterization of the speaking style in dubbing and the profile of the dubbing professional